Drug Interactions of Green Tea - Mahsa Meyboodi; Amir Hooshang Mohammadpour; Seyed Ahmad Emami; Hedyieh Karbasforooshan (Research Center for Rational Use of Drugs (RCRUD), 2020)
Green tea (GT) is among the most common drinks in the world. There are some reports on interactions between GT and some drugs. This paper attempts to provide a comprehensive review of this subject. The data are collected by searching PubMed, Scopus, Web of science, and Embase. The keywords used as search terms are "camellia sinensis", "pharmacodynamics", "pharmacokinetic", "EGCG", and "drug interaction". We have found 24 eligible articles. Finally, the related papers are given in our review. GT is containing polyphenols that interfere with many drugs. The most important of these polyphenol compounds is epigallocatechin-3-gallate (EGCG), which most of the reported interactions are due to the presence of EGCG. Interaction of GT with different drugs occurs in the context of both pharmacodynamics and pharmacokinetics that includes drug absorption, metabolism, and renal excretion. The mechanisms of these interactions consist of increase in the concentration included several medications such as melatonin, midazolam, and amlodipine consuming after GT; these interactions can be toxic. Additionally, it has been reported that serum levels of several drugs such as nadolol, digoxin, amoxicillin, and clozapine are decreased and their efficacy are reduced when they simultaneously administer with GT. The serum concentration of rhodamin 123, quinidine, and doxorubicin have increased when these drugs were co-administered with GT. GT has pharmacodynamics interactions with a few drugs such as a hydrochlorothiazide. As proposed and discussed here, GT has the potential for interactions with numerous other drugs and thus clinicians should be aware of reported and potential interaction of GT with various medications in order to avoid adverse reactions and achieve expected clinical response.